Interaction of legislation and prevalence of sexually transmitted diseases with focus on syphilis and gonorrhoea in the Czech Republic - review to year 2003 - Resl, V; Kumpová, M (Journal of the European Academy of Dermatology and Venereology, 2005)
INTRODUCTION: A large increase in syphilis prevalence was noted in the Czech Republic during the last decade. It was associated with prostitution in cities and especially in areas bordering more economically developed countries. Foreigners account for more than 50% of this increase. Absence of legislative regulations contributes to this situation. OBJECTIVE: To demonstrate the necessity of setting sexually transmitted disease (STD) fighting priority in the Czech Republic. METHODS: The authors review the development of legislation related to STDs in the context of geopolitical changes and the epidemiological situation in the Czech Republic by relating epidemiological, geopolitical and economic data. RESULTS: Venereal-diseases-related regulatory codes have existed in the Czech Republic for years; however, they became fragmented in several regulations and often do not have the status of law. It is a consequence of the transformation of the entire state health care delivery system to a private system. The treatment of foreigners, refugees and uninsured people is a major problem. CONCLUSION: It is necessary to focus on special populations, such as homeless people, immigrants and prostitutes. It is desirable to strengthen international cooperation in combating STD as well as prostitution. Relevant legislation should be introduced to correlate the existing regulations and bring them up to date.
Keywords: Sexually Transmitted Diseases; veřejné zdravotnictví; Female; Prevalence; ženské pohlaví; Sex Work; lidé; syfilis; Public Health; sexuálně přenosné nemoci; prevalence; gonorea; Male; Gonorrhea; Czech Republic; Syphilis; Česká republika; mužské pohlaví; prostituce; Humans